Validation of a training protocol for Marcha contests of the Mangalarga Marchador breed - Abrantes, Renata Guimarães Pequeno (2015)
The Mangalarga Marchador breed is functionally evaluated through marcha contests. The present research aimed to verify the efficacy of a training protocol for conditioning Mangalarga Marchador horses for marcha contests. Eight mares were used in a completely randomized block split-plot design, where each animal was a block, the physical tests (T I, T II, T III, T IV and T V) every 21 days of training were the plots, and the time of evaluation and collection of samples inside each test were the split-plots. The mares were trained for 84 days for one hour a day, five days a week, with rest on Saturdays and Sundays. On Mondays, Wednesdays, and Fridays, the animals warmed up in an oval track by walking for 10 minutes and then marching for a period established individually through a marcha test. Next, the animals were led in walk gait until an hour of exercise was completed. On Tuesdays and Thursdays, the animals were trained outdoors for one hour only walking. The tests consisted of successive 10 minutes stages at marcha, which was interrupted when heart rate reached 150 beats per minute and lactate levels were greater than 4 mmol/L, or after 70 min of the test. Marcha duration, heart rate and blood concentrations of lactate were evaluated. The results were submitted to an analysis of variance and the averages were compared by Fisher’s test at 5% probability. From zero at nine weeks of training, marcha duration increased progressively (p < 0.05), but there was no difference (p >0.05) between nine and 12 weeks of training. The training protocol used was appropriate to condition Mangalarga Marchador equines to compete in marcha contests following the rules of Brazilian Association of Mangalarga Marchador Breeders.